Beazley as theorist - Whitley, James
Sir John Beazley (1885-1970), founder of the modern and archaeological study of Classical vases, was a master of method. Is the Beazley method just that, a well-judged method fitting to the material under study? Or does that considered method in truth amount to a considered theory, held and used by a consciously most untheoretical archaeologist?